(untitled) (Research, Society and Development, 2022)
The objective of this study was to investigate the perception of bodybuilders about strength training as a protective factor against injuries. This is an observational, cross-sectional study with a quantitative approach to the data. The sample, not stratified by convenience, was composed of adult individuals, of both sexes, who practiced strength training in a studio located in the city of Campo Grande/MS. Data collection took place from September to October 2021, through an online form, distributed to study participants through a message application. Sociodemographic data and the perception of individuals regarding the protective capacity of strength training against injuries were collected. Eighty people participated in the study, with ages ranging from 19 to 57 years (29.9±7.4 years) and bodybuilding practice ranging from two months to 30 years (5.7±5.9 years). There was a higher prevalence of female individuals (62.5%), aged between 18 and 40 years (90.0%), single (66.3%), belonging to classes C, D and E (90.0 %), bodybuilders for more than 1 year (71.3%), with a weekly frequency of 3 to 5 days (78.7%), with sessions lasting up to 1 hour (87.5%), in search of health (85.0%). Almost half of the participants (45.0%) reported the presence of injuries, with the knees being the most affected region (23.8%), followed by the lumbar spine (11.3%), shoulders (11.3%) and ankle/feet (10.0%). Most believe that strength training contributes to preventing or improving injuries (98.8%), due to muscle and joint strengthening and improvement in physical conditioning (66.3%) and supervised and individualized monitoring (25.0%). The evaluated group understands that strength training, when performed under personalized professional guidance, acts to protect against injuries, as physical exercises improve muscular and osteoarticular physical fitness.